Primary squamous cell carcinoma of the fallopian tube masquerading inflammatory mass - Chawla, Indu; Bhardwaj, Minakshi; Ahuja, Arvind (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Primary squamous cell carcinoma (SCC) of fallopian tube is exceedingly rare. Till date less than 10 cases have been reported to the best of our knowledge [2-10]. Serous adenocarcinoma is the most common primary malignancy arising from the fallopian tube. Primary SCC of fallopian tube is diagnosed after excluding invasion from the rest of the genital tract and metastasis. We are reporting this rare carcinoma in a 62- year -old female who was taken for laparotomy with pre-operative diagnosis of tubo-ovarian abscess.